Measuring of the heifers ovaries and probiotic defence of the mucous membranes : ст. - Roman, L. et. al.; Гутий, Б. В. (Odessa State Agrarian University, Odessa, Ukraine ; Stepan Gzhytskyi National University of Veterinary Medicine and Biotechnologies Lviv, Lviv, Ukraine, 2022)
The results of the influence of complex probiotic defence of the mucous membranes of the reproductive system and intestines on the development of the corpus luteum of the cycle in heifers have been presented. By the method of differential palpation diagnostics in vivo, it was reliably examined that in the experimental group after carrying out procedures for the normalization of mucous membranes with the multicomponent probiotic drug “Multibacterin Veterinary Ba + La”, the number of heifers with highquality of corpus luteum the ovaries was 48.21% more, and the number of cases of premature luteolysis was 12.50 % less (P < 0.01). The level of pregnancy in heifers in the experiment was on average 60.38 %, in the control – 46.94 %, which confirmed the positive effect of the probiotic protection of the mucous membranes on increasing the embryo survival by optimizing the conditions for embryonic nutrition on the surface of the endometrium.
Keywords: heifers ovaries; heifers; телиці; пробіотичні препарати; probiotic defence